Cefiderocol and Sulbactam-Durlobactam against Carbapenem-Resistant Acinetobacter baumannii - Arta Karruli; Antonella Migliaccio; Spyros Pournaras; Emanuele Durante-Mangoni; Raffaele Zarrilli (MDPI AG, 2023)
Infections caused by carbapenem-resistant Acinetobacter baumannii (CRAB) remain a clinical challenge due to limited treatment options. Recently, cefiderocol, a novel siderophore cephalosporin, and sulbactam-durlobactam, a bactericidal β-lactam-β-lactamase inhibitor combination, have been approved by the Food and Drug Administration for the treatment of A. baumannii infections. In this review, we discuss the mechanisms of action of and resistance to cefiderocol and sulbactam-durlobactam, the antimicrobial susceptibility of A. baumannii isolates to these drugs, as well as the clinical effectiveness of cefiderocol and sulbactam/durlobactam-based regimens against CRAB. Overall, cefiderocol and sulbactam-durlobactam show an excellent antimicrobial activity against CRAB. The review of clinical studies evaluating the efficacy of cefiderocol therapy against CRAB indicates it is non-inferior to colistin/other treatments for CRAB infections, with a better safety profile. Combination treatment is not associated with improved outcomes compared to monotherapy. Higher mortality rates are often associated with prior patient comorbidities and the severity of the underlying infection. Regarding sulbactam-durlobactam, current data from the pivotal clinical trial and case reports suggest this antibiotic combination could be a valuable option in critically ill patients affected by CRAB infections, in particular where no other antibiotic appears to be effective.